2015
DOI: 10.1186/s40545-015-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical supply chain risk assessment in Iran using analytic hierarchy process (AHP) and simple additive weighting (SAW) methods

Abstract: ObjectivesPharmaceutical supply chain is a significant component of the health system in supplying medicines, particularly in countries where main drugs are provided by local pharmaceutical companies. No previous studies exist assessing risks and disruptions in pharmaceutical companies while assessing the pharmaceutical supply chain. Any risks affecting the pharmaceutical companies could disrupt supply medicines and health system efficiency. The goal of this study was the risk assessment in pharmaceutical indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 26 publications
1
107
0
4
Order By: Relevance
“…Many risks reported in studies [5,9] were defined as internal risks of the companies resulting from internal processes, employees, mismanagement etc. After ISO classification [14], which is also included in the risk catalog [15], these kinds of risks are categorized among operational risks.…”
Section: Debatementioning
confidence: 99%
See 3 more Smart Citations
“…Many risks reported in studies [5,9] were defined as internal risks of the companies resulting from internal processes, employees, mismanagement etc. After ISO classification [14], which is also included in the risk catalog [15], these kinds of risks are categorized among operational risks.…”
Section: Debatementioning
confidence: 99%
“…It turned out that the mentioned researsh was later the basis of future study in which Jaberidoost, Olfat, Hosseini et al performed the interviews with experts from Iranian pharmaceutical companies. In addition they identified 86 risks quality [9], of which 50 were already the subject of previous research [5], and 36 risks were newly identified. Risks were divided into 11 categories.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One of MADM methods is Simple Additive Weighting (SAW). This method [12] is also known as a weighted linear combination or scoring method. It is simple and the most often method used multi-attribute decision technique.…”
Section: Introductionmentioning
confidence: 99%